Material Selection by PJOK Teachers Based on Basic Motoric Competence in Elementary Schools - Arnaz Anggoro Saputro (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
The purpose of this study was to find out the choice of PJOK material based on the curriculum in small classes by PJOK teachers. This study used a quantitative descriptive method with 22 lower-class PJOK teachers as subjects in elementary schools in Jombang District. The collection of data used is a non-test instrument in the form of a questionnaire and interviews. Research data is converted into a percentage. From the results of the data analysis, it was found that the choice of learning materials for elementary school PJOK teachers in Jombang District for grade 1 received a percentage of 50 percent, grade 2 received a percentage of 45 percent, and grade 3 received a percentage of 48 percent. It was concluded that small-class PJOK teachers in Jombang District had selected, implemented, and presented materials to students in order to achieve the curriculum, and the selection of PJOK materials in elementary schools in Jombang District had reached the minimum standards set in the teacher's book and student book. The following factors influence the choice of PJOK teacher material: infrastructure and teacher competence.